Conduct Of Youth In Connection With Online and Offline Shopping: A Relative View - Deepak Sood, Kavita Sharma, Sachin Sharma (International Journal of Advanced Science and Technology, 2020)
Shopping is a major aspect of the every person’s life. Some have the bare essentials for shopping, others have a little more. It is considered as a way to relieve stress, quench a craving, or give a taste to the mechanical way of life. Shopping is also considered as a source to relieve stress. This report expands the studies while asking consumers interested in online shopping and traditional shopping to evaluate performance channels for goods their deliverance time with value to products. By embracing this approach, researcher and expert can put on important information for reasons of adopting the defined channel with purchasing. With the help of various statistical techniques it has found here that because of extensive revolution of information technology and other technical know-how the youth prefer the same.